"Caridade sem limites. Sciência sem privillegios" : o ensino universal de Jacotot por Benoît Mure no Brasil (1840-1848) - Cruz, Crislaine Santana (2018)
This research intends to analyze the actions undertaken by the intellectual, homoeopathic and utopian socialist, Benoît Jules Mure (1809-1858), for the dissemination of the Method of Universal Teaching while he was in Brazil, bearing in mind that this Method presupposes equality between human intelligences and which was discovered by the French pedagogue Jean-Joseph Jacotot (1770-1840) in the year 1818 gaining notoriety in several regions of Europe, one can see its circulation also in nineteenth-century Brazil. The time frame used here is justified, therefore, it comprises the period of 1840, the year in which Mure landed in the country, in 1848, the date on which it left, and marks its passage in Brazilian lands. It is worth mentioning that this research is based on the presuppositions of the History of Education, in the perspective of Cultural History. The research uses as sources, non-pedagogical periodicals that circulated in the province of Rio de Janeiro during the period. Especially the Jornal do Commercio of Rio de Janeiro, founded in 1827 and also A Sciencia: Synthetica Magazine of Human Knowledge, a production of Mure himself and his group of adepts with periodical publication from 1847 to 1848. The sources worked here were found in archives online from the National Library of Brazil. It is noteworthy that Benoît Mure acted in different ways in favor of the dissemination of Universal Teaching, from publications about the Method, to its application in the Homeopathic School of Brazil. We hope that this analysis represents an important contribution to the historical knowledge of the Method of Universal Teaching in Brazil, making possible the broadening of the field of Education History, since it is an unexplored subject in Brazilian educational historiography.